THE EFFECT OF PROBLEM-BASED LEARNING METHOD ON STUDENTS' CRITICAL THINKING ABILITY - Iskandar Iskandar; Eman Sulaeman Al Fathan (Indonesian Journal of Learning and Instruction, 2021)
The purpose of this study was to determine the effect of using problem-based learning methods on students' critical thinking ability with emotional intelligence as a moderating variable in 11th Grade Students of Social Studies at Al Islam Boarding School Senior High School, Kondangsari Village, Beber Sub District, Cirebon District. The research method used was a quasi-experimental with a factorial design. The subjects of this study were 66 students of 11th Grade Students of Social Studies (XI IPS) at Al Islam Boarding School Senior High School, Kondangsari Village, Beber Sub District, Cirebon District where the XI IPS 2 class was the experimental class and the XI IPS 3 class was the control class. The data analysis technique used the two-way ANOVA test. Based on the research results, it was known that there a significant effect of using problem based learning methods on critical thinking ability, there is significant effect of emotional intelligence on critical thinking ability, and there is significant interaction effect between the using problem based learning methods and emotional intelligence on students' critical thinking ability of 11th Grade Students of Social Studies at Al Islam Boarding School Senior High School, Kondangsari Village, Beber Sub District, Cirebon District. Therefore that emotional intelligence moderates the effect of using problem based learning methods on critical thinking ability.Keywords: problem based learning methods; emotional intelligence; critical thinking ability